Adherence to prescribed antihypertensive medications and associated factors for hypertensive patients attending chronic follow-up units of selected public hospitals in Addis Ababa, Ethiopia - Tibebu, Abel; Mengistu, Daniel; Bulto, Lemma Negesa (International Journal of Health Sciences, 2017)
Objectives: The study was aimed at assessing adherence to prescribed antihypertensive medications and its associated factors. Methodology: Institutional-based cross-sectional study was conducted in four public hospitals which were selected by lottery method. Systematic random sampling was used to select the study subjects. Data were checked, cleaned, and entered into Epidata software version 3.1 and were imported to SPSS version 21 software for analysis. The results of the descriptive statistics were expressed as percentages and frequencies. Associations between independent variables and dependent variable were analyzed using bivariate and multivariate analysis. The study was conducted from February 15 to April 15, 2016. Results: The study included 404 respondents with 97% response rate. 210 (52%) were male and mean age was 54 ± 10.77 years. The respondents’ adherence to antihypertensive medications was 66.8%. The medication-related adherences were found to be better in females, patients who had comorbidities and have been knowledgeable about the disease and was poor among young adult respondents. Conclusion: This study found out a 66.8% adherence to prescribed antihypertensive medications. This figures show that medication adherence (MA) rates are low. The factors impeding or enhancing the outcome variable was thoroughly analyzed. Sex, age, number of types of medications, and knowledge were associated with MA. Educational sessions that especially focus on MA and ongoing support for patients should be designed. Studies which assess all the components of self-management should be conducted for comparison among different subgroups.